2010
DOI: 10.1373/clinchem.2009.134460
|View full text |Cite
|
Sign up to set email alerts
|

High-Sensitivity Cardiac Troponin T for Early Prediction of Evolving Non–ST-Segment Elevation Myocardial Infarction in Patients with Suspected Acute Coronary Syndrome and Negative Troponin Results on Admission

Abstract: BACKGROUND:We sought to determine the diagnostic performance of the new high-sensitivity cardiac troponin T (hs-cTnT) assay for early detection of non-STsegment myocardial infarction (NSTEMI) in patients with acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
190
5
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 310 publications
(218 citation statements)
references
References 20 publications
13
190
5
10
Order By: Relevance
“…The 10% coefficient of variation is less than this value 21, 22. In total, 93.2% of participants had hsTnT ≥3 ng/L.…”
Section: Methodsmentioning
confidence: 85%
“…The 10% coefficient of variation is less than this value 21, 22. In total, 93.2% of participants had hsTnT ≥3 ng/L.…”
Section: Methodsmentioning
confidence: 85%
“…Several factors affect hs-cTnT concentrations including extracellular volume [13], cardiac rhythm [14], myocardial ischaemia [15], and the dialysis prescription [16,17]. These influences were assessed using a structured clinical interview, physical examination and medical records review to ascertain interim hospitalisation, changes to medication and/or the dialysis prescription.…”
Section: Patient Assessmentmentioning
confidence: 99%
“…Overall, these findings supported the use of troponin as the biomarker of choice in risk stratification, and NACB advocated and recommended its measurement in all patients with suspected ACS. A troponin concentration above the 99th percentile is an indicator of death and an increased risk of recurrent ischemic events (Giannitsis et al, 2010). Cardiac troponin is the preferred marker for myocardial injury in the new guidelines for the diagnosis and treatment of non-STsegment elevation ACS (Apple et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The role of high-sensitivity cTnT (hs-cTnT) in myocardial ischemia has been demonstrated in many studies; hs-cTnT has recently become commercially available (Laufer et al, 2010) and is being produced and distributed by Roche for clinical applications. One report showed that even mild coronary artery disease was associated with quantifiable circulating levels of hs-cTnT in patients without acute coronary syndrome (ACS) (Laufer et al, 2010), whereas other research revealed its function in the prediction of evolving non-ST-segment elevation myocardial infarction among patients with suspected ACS and negative troponin on admission (Giannitsis et al, 2010). However, there is insufficient evidence to support the diagnostic sensitivity and specificity of cTnT for the detection of myocardial ischemia.…”
Section: Introductionmentioning
confidence: 99%